Reassessing (home-)regionalisation - Osegowitsch, Thomas; Sammartino, André (Journal of International Business Studies, 2008)
Alan Rugman and co-authors argue that globalisation, and with it global strategy, is a myth. This contention rests on a taxonomy of the world's largest firms based on their sales, showing an overwhelming share of home-regional firms. We question the rationales underpinning their classification scheme. When retesting the data using different schema we find that the original results are far from robust, with a significant share of firms attaining bi-regional or global status. Further longitudinal analysis shows that large firms increasingly are extending their sales beyond the home region. Our results defy regionalisation theory in its current form, and we call for refinements through further research.